Habenaria fimbriatiloba (Orchidaceae), a new orchid species from China - Kolanowska, Marta (Phytotaxa, 2015)
Since it was published, Habenaria Willdenow (1805: 5) has become one of the largest and the most widespread genera of Orchidaceae. The estimated number of species included in the genus is over 800 (Govaerts et al. 2010), but novelties are published frequently (eg. Batista et al. 2012, Karthigeyan et al. 2014, Murugan et al. 2014). The highest specific diversity of Habenaria is observed in Brazil, southern and central Africa and East Asia (Kurzweil & Weber 1992), but species are found in most tropical and subtropical regions.